Emergent laparoscopic sigmoid resection for perforated diverticulitis: can it be safely performed by residents?. (3rd February 2020) - Dreifuss, N. H.; Schlottmann, F.; Bun, M. E.; Rotholtz, N. A.
Abstract: Aim: Outcomes after resident involvement in emergent colectomies have rarely been studied. The aim of this study was to analyse the outcomes of laparoscopic sigmoidectomy for Hinchey III diverticulitis performed by residents. Method: This study was a retrospective analysis of patients undergoing laparoscopic sigmoidectomy for diverticulitis. The sample was divided into two groups: patients operated on by a supervised resident (SR) or a senior surgeon (SS). Supervising surgeons and SSs could be general surgeons (GSs) or colorectal surgeons (CSs). A SR was considered the first surgeon if he/she completed at least three of five defined steps of the procedure. The primary end‐points included length of hospital stay (LOS), morbidity and 30‐day mortality. A sub‐analysis of patients operated on by a SR assisted by either a CS or GS was performed. Results: Supervised residents and SSs operated on 59 and 42 patients, respectively. The presence of a CS was more frequent in the SS group (SR 41% vs SS 81%, P  < 0.001). LOS (SR 9.4 days vs SS 6.4 days, P  = 0.04) was higher in the SR group. Overall morbidity (SR 39% vs SS 43%, P  = 0.69) and 30‐day mortality (SR 5% vs SS 5%, P  = 0.94) were also comparable among the groups. Procedures performed by SRs and supervised by a CS were associated with lower morbidity (GS 48% vs CS 25%, P  = 0.06) and mortality (GS 8% vs CS 0%, P  = 0.26). Conclusion: Laparoscopic sigmoidectomy for Hinchey III diverticulitis has comparable outcomes when performed by a supervised SR or a SS. Procedures performed by residents assisted by a CS seem to have better outcomes than those assisted by a GS.